Health profile of adult beedi workers among unorganized sectors in Kolar city - S., Harish; Kamath, Prasana (International Journal Of Community Medicine And Public Health, 2024)
Background: Over 35 million people are involved in tobacco industry. Beedi rolling causes serious occupational health hazards to the workers and their family who are constantly exposed to tobacco dust and hazardous chemicals, compounded by factors at the place of work. Occupational diseases due to inhalation of tobacco dust and the other is the result of long hours of continuous sitting in an improper working posture. Methods: A cross-sectional study was done among adult beedi workers residing in Kolar city. The study included 384 beedi workers. A pretested, semi-structured questionnaire was used to collect data. Results: The study comprised of 384 study subjects out of which, Among the health problems, most common were musculoskeletal problems involving 277 (72.02%) subjects, followed by respiratory problems among 159 (41.40%), eye problems among 46 (11.9%) and others 23 (5.9%). Most common chronic illness were found to be Hypertension in 43 (43.88%) followed by Asthma 26 (26.53 %), Diabetes mellitus 12 (12.24%), ischemic heart disease 7 (7.4%) and others 10 (10.20%). Lung functions were assessed by spirometry in 83 study subjects of whom 9.6% were having obstructive features, followed by 2.4% with restrictive features, 3.6% having mixed. Conclusions: Musculoskeletal problem was the most common morbidity. Which was related to the working posture of continuous forward bending of the trunk. Educational status of such workers was found to play an important role in creating awareness and in turn utilization of welfare schemes.